The activity of class I, II, III and IV alcohol dehydrogenase isoenzymes and aldehyde dehydrogenase in the sera of bladder cancer patients - Orywal, Karolina; Jelski, Wojciech; Werel, Tadeusz; Szmitkowski, Maciej (Acta biochimica Polonica, 2017)
Studies on alcohol dehydrogenase (ADH) and aldehyde dehydrogenase (ALDH) activity in the sera of patients with malignant neoplasms show that cancer cells in many organs may release ADH isoenzymes into the blood. The aim of this study was to investigate the differences in the activity of ADH isoenzymes and ALDH in the sera of patients with bladder cancer (BCa), and with different grades of the disease. Blood samples were taken from 39 patients with BCa (15 patients with low-grade and 24 with high-grade BCa) and from 60 healthy subjects. Class III and IV of ADH and total ADH activity were measured using the photometric method, while class I and II ADH and ALDH activity using the fluorometric method with class-specific fluorogenic substrates. The activity of the class I ADH isoenzyme and total ADH was significantly higher in the sera of BCa patients as compared to control group. Analysis of ALDH activity did not show statistically significant differences between the tested groups. Significantly higher total activity of ADH in comparison to control was found in both, low-grade and high-grade BCa group. The activity of ADH class I was also significantly higher in high-grade BCa group when compared to low-grade patients and controls. The increase of total ADH activity in the sera of BCa patients seems to be caused by isoenzymes released from cancerous cells. The higher activity of ADH I probably resulted from metastatic tumors as significant increase was detected only in the sera of high-grade bladder cancer patients.